FACTORS INFLUENCING THE CHOICE OF FDI LOCATIONS IN TURKEY - Lale Berkoz; Sevkiye Sence Turk (European Regional Science Association (ERSA), 2005)
Turkey adopted neo-liberal policies in order to increase economic integration into international relation after 1980. As a result of these policies, foreign direct investment (FDI) inflows increased greatly. In 1980 there were 78 FDI firms in Turkey whereas the number increased by 9749 at the end of 2004. Turkey has become a hub of vast hinterland that extends from Balkans to Caucasus and represented a prime focus for foreign investment. For this reason, it is very important to know the characteristics and spatial distribution of FDI firms in Turkey. This study analyzes the spatial distribution of FDI (foreign direct investment) firms among the provinces in Turkey from 1990 to 2004. A model is developed to test the agglomeration economies as a demand, urbanization economies, market size, employment structure, government incentivies, information cost, locational wealth and infrastructure. The results support that agglomeration economies resulting from the concentration of manufacturing activities and density in the provinces; information cost and market size are stronger locational determinants in Turkey.
Keywords: 330